Anti‐Hu‐Associated Autoimmune Limbic Encephalitis in a Patient with PD‐1 Inhibitor‐Responsive Myxoid Chondrosarcoma. (20th November 2017) - Papadopoulos, Kyriakos P.; Romero, Rebecca S.; Gonzalez, Gabriela; Dix, James E.; Lowy, Israel; Fury, Matthew
Abstract : Autoimmune encephalitis is an uncommon complication of immune checkpoint inhibitor therapy. This article reports a case of fatal anti‐Hu‐associated autoimmune limbic encephalitis presenting within 8 weeks following anti‐PD1 therapy in a patient with myxoid chondrosarcoma and pre‐existing anti‐Hu antibodies. Although tumor reduction occurred in response to PD‐1 inhibitor therapy, the patient had a rapidly progressive decline in neurologic function despite initial stabilization with immunosuppression. Considering the increasing use of immune checkpoint inhibitors for the treatment of various malignancies, an increase in the occurrence of neurologic adverse events is likely, requiring prompt intervention and enhanced pharmacovigilance in malignancies associated with onconeuronal antibodies. Abstract : A case of fatal anti‐Hu‐associated autoimmune limbic encephalitis in a patient with myxoid chondrosarcoma treated with a PD‐1 inhibitor is reported.